How to be an effective interviewer (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. It's as simple as this - if your interview process is poorly designed or off-putting to candidates, they will look elsewhere for opportunities. Today we'll cover the value of proper preparation, forefronting empathy, good note-taking, active listening and selecting the right questions. We'll finish with an important note about unconscious bias. Let's talk about how to maximise your business' chances of securing the hottest prospects in the market! Learning Objectives Discover how to be an effective interviewer Learn the value of proper preparation, forefronting empathy, good note-taking, active listening, avoiding unconscious bias, and selecting the right questions.